PENGARUH KOLEKTIVISME, LOCUS OF CONTROL, DAN INSENTIF PADA PERILAKU MENDAUR ULANG SAMPAH - , Rina SariQurniawati, Dr. B.M. Purwanto, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
World population growth was accompanied by increasing the amount of waste generated by households. This waste will result in the destruction of the environment if not managed properly. Public awareness of natural disaster caused by the garbage is not followed by their behavior to recycle the waste that they generate. Collectivism and internal locus of control as a basic human value orientation that associated with a personâs interaction with the surrounding environment affects the recycling behavior. These basic values will affects the psychological construct that is more specific beliefs about recycling. Incentives are also important in explaining recycling behavior. This study aims to examine the influence of value orientations (collectivism and internal locus of control) on beliefs about recycling (the importance and inconvenience of recycling). This research also aims to investigate the influence of recycling intention and incentive on recycling behavior. Hypotheses are developed and tested using data from a survey study among 328 household in DKI Jakarta and Salatiga. The study was based on confirmatory model. SPSS statistical model used to test validity and reliability of the instrument. Structural equation modeling (SEM) by using AMOS statistical program used to test the goodness of fit model and the relationship hypothesized in the theoretical model proposed. Findings from structural models have proved nearly all the hypothesized relationships. Internal locus of control proved influential on beliefs about importance of recycling but the effect of collectivism on beliefs about importance of recycling is not supported. Beliefs about inconvenience of recycling proved has negative effect on recycling behavior while belief about importance of recycling on effect on recycling behavior is not supported. Incentive proved influential on recycling behavior.